Implementation of Lean Manufacturing With A Value Stream Mapping Approach to Improve The Efficiency of The Production Process - Setiawan, Ferry (Universitas Al Azhar Indonesia, 2022)
This research is based on the fact that many domestic sugar industries operate inefficiently and have low productivity, which is seen when compared to other countries such as Thailand, India and Australia. This study aims to identify and analyze problems along the flow of the white crystal sugar production process that cause waste and then make suggestions for improvements to reduce existing waste to increase cost efficiency in the production process. The national sugar factories generally have a basic problem, namely the low level of factory efficiency, which causes a lot of waste along the flow of the production process. The right concept for solving this problem is the implementation of the Lean manufacturing method, where this method focuses on efforts to reduce waste along the flow of the production process by making continuous improvements. The research begins with a literature study and field study and then conducts observations, analyzes, brainstorms, extracts and collects data from each work unit. The first stage begins with the define which will identify all forms of waste along the production process flow, measure to determine the most critical waste, analyze to identify the factors that cause waste in the production process, improve to carry out improvement plans, and reduce waste that occurs in the production process, and control as an evaluation of improvement results. The efficiency of the production process before the improvement is 78.7%, with improvements expected to increase production efficiency by 87.0% or an increase of 8.3 points.Keywords - Lean Manufacturing, DMAIC, Value Stream Mapping, Waste, Production Efficiency